2004
DOI: 10.1038/sj.jhh.1001681
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of nocturnal blood pressure fall in early phases of untreated essential hypertension: a prospective observational study

Abstract: A number of studies have shown that a smaller than normal nocturnal blood pressure (BP) decrease is associated with cardiovascular disease. However, no large prospective studies have examined the reliability of nocturnal dipping within individuals. The aim of our study was to investigate the short-term variability of nocturnal BP fall in a large cohort of patients with recently diagnosed essential hypertension. In all, 414 uncomplicated never treated hypertensive patients referred to our outpatient hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 33 publications
3
50
0
Order By: Relevance
“…First, MNHT status was determined according to a single ambulatory BP measurement. The high degree of intra-individual variation of nocturnal BP patterns in patients with hypertension [27] means that it could be argued that repeated ambulatory BP measurements are needed in order to determine the true prevalence of MNHT. However, it was recently shown that short-term reproducibility of nocturnal BP patterns is higher in patients with type 2 diabetes (88.9%) than in patients without diabetes (70.5%) [28].…”
Section: Discussionmentioning
confidence: 99%
“…First, MNHT status was determined according to a single ambulatory BP measurement. The high degree of intra-individual variation of nocturnal BP patterns in patients with hypertension [27] means that it could be argued that repeated ambulatory BP measurements are needed in order to determine the true prevalence of MNHT. However, it was recently shown that short-term reproducibility of nocturnal BP patterns is higher in patients with type 2 diabetes (88.9%) than in patients without diabetes (70.5%) [28].…”
Section: Discussionmentioning
confidence: 99%
“…Another problem when evaluating dipping or nondipping status is the limited reproducibility of nocturnal BP variability. This limitation is related to changes in day activities and sleep quality, besides the "regression to the mean" phenomenon that occurs when repeating ABPM in patients previously classified as extreme dippers or nondippers and risers (33,34). Otherwise, the reproducibility of dipping status was recently reported to be more reliable in diabetic than in nondiabetic hypertensive patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…19 This long-term reproducibility was comparable with the short-term reproducibility of nondipping status between 2 ambulatory blood pressure recordings repeated within 4 weeks. 23 To the best of our knowledge, only 1 study compared the short-term reproducibility of nocturnal hypertension and nocturnal dipping status defined according to absolute blood pressure level and relative day-to-night blood pressure changes, respectively. 24 In an analysis in hypertensive patients who enrolled in a placebo-controlled clinical trial and had 2 repeated ambulatory blood pressure recordings 4 to 8 weeks apart, the reproducibility of nocturnal hypertension (≥125/80 mm Hg, κ statistic ≥0.46) was much higher than that of nocturnal nondipping (<5% or <10% of daytime blood pressure, κ statistic ≤0.38).…”
Section: Reproducibilitymentioning
confidence: 99%